MNE competence‐creating subsidiary mandates - Cantwell, John; Mudambi, Ram (Strategic Management Journal, 2005)
The determinants of R&D intensity differ between subsidiaries in a multinational enterprise (MNE). Previous literature suggests that whether a subsidiary achieves a competence‐creating output mandate depends on the qualities of its location. R&D strategies in competence‐creating subsidiaries are supply‐driven while those in purely competence‐exploiting subsidiaries are demand‐driven. Using data on U.K. subsidiaries of non‐U.K. MNEs, we find that the level of subsidiary R&D depends on MNE group‐level and subsidiary‐level characteristics as well as locational factors. The R&D of mandated subsidiaries rises with acquisition, but for non‐mandated subsidiaries R&D falls upon acquisition. MNEs that grow through acquisition have more inter‐subsidiary R&D diversity. Copyright © 2005 John Wiley & Sons, Ltd.